The organisation of exchange control in Italy - VERNUCCI, A. (PSL Quarterly Review, 2014)
The present article, which is of a technical and descriptive nature, surveys the organisation of exchange control in Italy. The author gives an account both of the bodies that are responsible for exchange control, and of the manner in which that control is carried out. JEL: F31, F38